Dynamic behavior of materials, volume 1 proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics - Song, Bo (Materials scientist); Casem, Daniel; Kimberley, Jamie (Springer, 2015)
Dynamic Behavior of Materials, Volume 1: Proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics, the first volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers on: · General Dynamic Materials Response · Novel Dynamic Testing Techniques · Dynamic Fracture and Failure · Dynamic Behavior of Geo-materials · Dynamic Behavior of Composites and Multifunctional materials · Dynamic Behavior of Low-Impedance materials · Dynamic Modeling and Simulation of Dynamic Behavior of Materials · Quantitative Visualization of Dynamic Behavior of Materials · Shock/Blast Loading of Materials · Interface and Structural Dynamics · Materia